PENGARUH MOTIVASI TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (Studi pada Mahasiswa Akuntansi Program S1 dan Program PPAk Universitas Brawijaya) - Andrias Nur Rochim; Lilik Purwanti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The objective of research is to validate empirically the effect of quality motivation, career motivation, and economic motivation on the interest of accounting students to follow PPAk and to compare what the motivation influences the interest to attend to PPAk among the accounting students of S-1 Program and PPAk Program. Research sample is 82 respondents, consisting of 52 accounting students of S-1 Program and 30 accounting students of PPAk Program. Data analysis method is multiple regression. Result of examination indicates that quality motivation, career motivation, and economic motivation significantly influence the interest of accounting students to attend to PPAk. Among accounting students of S-1 Program, a motivation influencing the interest to attend to PPAk is career motivation, while among accounting students of PPAk program, a motivation influencing their interest for PPAk is quality motivation and career motivation. Keywords: Quality Motivation, Career Motivation, Economic Motivation, Interest, Accounting Profession Education